2016
DOI: 10.5539/gjhs.v8n12p1
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence and Its Related Factors Based a Prevalence Study in Iran

Abstract: The aim of present study was to assess the frequency of violence against married women and its related factors in health centers affiliated to Isfahan University of medical sciences. This is a cross-sectional study was conducted on married women who were attending in health centers in Isfahan city, Iran. Woman Abuse scale was used to illicit information regard to violence and a structured questionnaire was used to gathering data regard to socio demographic characteristics. Out of the total 600 women (61.7%) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…This finding was confirmed with previous research conducted in Iran. Abbaspoor et al (2016) indicated that 61.7% of women in the study reported domestic violence and psychological violence was the most prevalent (59.7%). In the study of Kargar-Jahromi et al (2016), 49.4% of women reported one type of violence of which the most common type was psychological violence (44.4%).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This finding was confirmed with previous research conducted in Iran. Abbaspoor et al (2016) indicated that 61.7% of women in the study reported domestic violence and psychological violence was the most prevalent (59.7%). In the study of Kargar-Jahromi et al (2016), 49.4% of women reported one type of violence of which the most common type was psychological violence (44.4%).…”
Section: Discussionmentioning
confidence: 87%
“…According to the WHO (2018), more than 753 million women worldwide have experienced physical or sexual violence from a partner (WHO, 2021). The conducted studies in Iran have shown that approximately 60% of women have experienced at least once the domestic violence (Abbaspoor & Momtazpour, 2016; Ahmadi et al, 2008; Hajnasiri et al, 2016). Violence against women has various consequences which can affect women’s health by causing physical injuries, psychosomatic and emotional disorders, and even death (Aghakhani et al, 2012; Holmes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Literatüre göre çocuk sayısının fazla olması şiddet görme riskini artıran etkenlerden biridir. 16,43 Çalışma-mızda, konukevinde kalan kadınların ortalama 1.8, evinde kalan kadınların ise 3.1 çocuğunun olduğu görüldü.…”
Section: Discussionunclassified
“…[ 2 ] Violence against women is considered as one of the violations of human rights that is not related to a specific geographical area or a specific social level and is seen in a comprehensive manner with all socioeconomic levels. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%